Real-space observation of the dissociation of a transition metal complex and its concurrent energy redistribution - Aviad Schori; Elisa Biasin; Ambar Banerjee; Sébastien Boutet; Philip H. Bucksbaum; Sergio Carbajo; Kelly J. Gaffney; James M. Glownia; Robert Hartsock; Kathryn Ledbetter; Andreas Kaldun; Jason E. Koglin; et al. (Nature Communications)
Abstract Mechanistic insights into photodissociation dynamics of transition metal carbonyls, like Fe(CO)5, are fundamental for understanding active catalytic intermediates. Although extensively studied, the structural dynamics of these systems remain elusive. Using ultrafast X-ray scattering, we uncover the photochemistry of Fe(CO)5 in real space and time, observing synchronous oscillations in atomic pair distances, followed by a prompt rotating CO release preferentially in the axial direction. This behavior aligns with simulations, reflecting the interplay between the axial Fe-C distances’ potential energy landscape and non-adiabatic transitions between metal-to-ligand charge-transfer states. Additionally, we characterize a secondary delayed CO release associated with a reduction of Fe-C steady state distances and structural dynamics of the formed Fe(CO)4. Our results quantify energy redistribution across vibration, rotation, and translation degrees of freedom, offering a microscopic view of complex structural dynamics, enhancing our grasp on Fe(CO)5 photodissociation, and advancing our understanding of transition metal catalytic systems.